Immune response to Hepatitis B vaccination in hemodialysis patients. - Kunwer Naveed Mukhtar; Syed Farrukh Umair; Sumbal Nasir Mahmood (ziauddin University, 2024)
Background: Hemodialysis patients are vulnerable to infections with Hepatitis B Virus and hepatitis C virus (HCV). Patients who are on maintenance hemodialysis are considered as high-risk group for acquiring hepatitis B virus, resulting in high morbidity and mortality. Therefore, to vaccinate them against the virus is mandatory. Compared to a response rate of over 90% in the normal population, only 50 to 60% of those with end-stage renal disease achieve adequate antibody levels following immunization and the objective of this study was to determine the antibody level after Hepatitis B vaccination in chronic hemodialysis patients. Methods: 118 patients, undergoing chronic hemodialysis (HD) at the dialysis unit of Liaquat National Hospital, fulfilling the inclusion and exclusion criteria were enrolled between April 2013 and September 2013, after taking informed consent and approval from ethical review committee. AntiHbs (Hepatitis B surface antibody) titers were measured. Patients were differentiated as Immune and non immune based on antibody titers, with levels of >10IU/l being considered as immune and levels of <10IU/las non immune. AntiHbs titer was measured by ELISA (Enzyme Linked Immunosorbant Assay). Data was analyzed using SPSS version 14.0 for windows. Chi square test were used to ascertain the statistical significance. P value <0.05 was taken as statistically significant. In addition, the effect of age, gender and duration of Hemodialysis on antibody titer was also observed. Results: Out of 118 patients enrolled, 103 (87.3%) had an adequate antibody response and were considered immune while only 15 patients (12.7%) had an inadequate antibody response rendering them non immune. AntiHbs titers showed no significant co-relation with gender and duration of Hemodialysis therapy(p>0.05), while age was found to have significant correlation as younger age group (<60years) had more immune response (p<0.001). Conclusion: Our study showed a very good antibody response to Hepatitis B vaccination among hemodialysis patients that correlated with age with younger age group having a better response but no correlation to gender and duration of dialysis. Key Words: Hepatitis B virus, Anti-HBs antibody, Hemodialysis, Prevalence, Vaccination.